Canine visceral leishmaniasis and Rhipicephalus sanguineus: evaluation and comparison of classical techniques - Santos-Doni, Thaís Rabelo; Viol, Milena Araúz [UNESP]; Lima, Valéria Marçal Felix [UNESP]; Oliveira, Bruno César Miranda [UNESP]; Matos, Lucas Vinicius Shigaki [UNESP]; da Costa, Alvimar José [UNESP]; Gomes, Jancarlo Ferreira; Bresciani, Katia Denise Saraiva [UNESP] (Springer Nature, 2022)
The aim of this study was evaluating the association and correlation between the diagnostics tests used for Leishmania spp. detection in dogs and ticks. We evaluated 99 dogs and 990 Rhipicephalus sanguineus. In dogs, we used bone marrow aspirates and lymph node fine-needle aspiration biopsy (FNAB) for direct parasitological examinations and real time-polymerase chain reaction (RT-PCR) and collected blood samples for enzyme-linked immunosorbent assays (ELISA). In ticks, two laboratory techniques [immunohistochemistry to lipophosphoglycan (IHC) and RT-PCR] were performed in the intestine, ovaries and salivary glands. With respect to the measurement of diagnostic performance in dogs, lymph node RT-PCR proved to be the best test followed by ELISA and bone marrow RT-PCR. In ticks, intestine IHC were considered as a gold standard for diagnosis of leishmaniasis with intestinal RT-PCR being the best diagnostic test. To arrive at the correlation between laboratory techniques for dogs and their ticks, we evaluated the diagnostic test used for dogs with tests performed in R. sanguineus, which used lymph node FNAB as the gold standard. The intestine IHC technique showed strongest association. We demonstrated that the best tissue for Leishmania spp. detection in dogs was the lymph node and the intestine in case of ticks. As for laboratory techniques, the isolated analysis of each species presented a strong agreement between immunohistochemistry and RT-PCR when compared to its gold standard. In addition, we concluded that the immunohistochemistry of ticks’ intestines was a better technique for diagnosing Leishmania spp. in R. sanguineus, thereby showing almost perfect correlation with the lymph node FNAB.
Keywords: Diagnostic; ELISA; Leishmania; RT-PCR; Smears; Ticks